Evaluation of the Independent Curriculum in Special Schools to Enhance Participation of Children with Special Needs - Sulaiman Abdul Rasid; M. Mukhibat; Rihab Wit Daryono (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
The independent curriculum aims to create an inclusive learning environment in special schools, where children with special needs are fully integrated into the learning process with their friends without barriers or discrimination. This research aims to evaluate the achievements of the independent curriculum in particular schools in increasing the participation of children with special needs in learning. This research uses an evaluation method using the CIPPO model developed by Stufflebeam and Shinkfield. The research instrument was shown to school principals, vice principals, and teachers as a questionnaire. Using random sampling techniques, 32 respondents were chosen, consisting of 3 principals, 7 vice principals, and 25 teachers. The findings of this research identify the lowest measurement of evaluation results, namely in the input aspect, namely the involvement of parents in decision making, support for facilities and infrastructure, and social support from friends need to be improved. So, the recommendation that needs to be improved is that schools and teachers must develop partnerships with community organizations and government institutions to support inclusion efforts, including providing additional services and social support for children with special needs. In addition, particular schools must prioritize providing information and training to parents, teachers, students, and the community about the importance of inclusion, the rights of children with special needs, and the best ways to support their participation in the learning process.